Controle modal de rotores com mancais magnéticos: Projeto Robusto - Borges, Adriano Silva (2016)
The present work is devoted to the development of a Systematic Approach for the Robust Design of an Active Modal Controller applied to Supercritical Rotors supported by Magnetic Bearings. For this purpose, all the steps involved in the design of a robust controller based on multimodel eigenstructure assignment technique were discussed from a complete and detailed point of view. The first step was the conception of a numeric/computer model in MATLAB/SIMULINK environment, based on the specifications provided by the test rig manufacturer. Following, this model was tested through an experimental validation process, resulting a mathematical model that represents closely the dynamic behavior of the actual physical system. Next, the most critical uncertainties of the system were incorporated into the nominal model by using the Linear Fractional Transformation (LFT) approach. The first stage of the controller synthesis process itself was the specification of all design requirements. Then, all the phases involved in the process of the multimodel eigenstructure assignment are addressed in detail, starting from the determination of the plant dominant poles until the model based analysis of the system stability and performance. In this way, the potential of the methodology proposed was investigated and possible design problems were anticipated. It should be highlighted that the system stability was assessed from two different viewpoints, namely the standard ISO 14839-3 and the structured singular values (μ-analysis). In the same way, the performance of the controller was evaluated through the analysis of its closed loop Transfer Functions and by investigating the unbalance response of the rotating system. The unbalance response was conducted according to the API 684 technical standard guidelines and the vibration severity was classified as based on ISO 14839-2 criteria. Therefore, both the stability margin and performance of the controller were experimentally assessed which, in accordance with the simulations, demonstrated that the controller design was successful. Based upon these results, it is possible to state that the main contribution of the presente work was the sistematization of the Robust Design of Active Modal Controller applied to Supercritical Rotors supported by Magnetic Bearings. In addition, anothers relevant contributions should also be highlighted, namely: development of representative models of rotating systems for application in active control plants, determination and implementation of active control architectures with real possibility of application in industry, design and characterization of controllers for active magnetic bearings with focus in modal control. Finally, it is worth mentioning that for all presented investigations, comparisons between the two architectures of the controller, namely: the modal controller and the PI controller were performed accordingly.